The effect of 5s practices by midwives on the comfort of pregnant women during examinations at ratte community health center - Asli, Kartika (Innovative Approaches in Health Science Journal, 2024)
Introduction: Patient comfort is an important factor in increasing visits to Puskesmas. The friendly service of the Puskesmas, the cleanliness of the room, and the neat layout of the room can make patients feel comfortable visiting. Objective: To find out the effect of 5s practices by midwives on the comfort of pregnant women when having examinations at the Ratte Puskesmas. Method: The type of research used is an Analytical Survey with a Cross Sectional Study approach. The samples in this study were all pregnant women who visited the Batusura Community Health Center in the last 1 year. The samples in this study were taken with a total sampling of 65 respondents. Data collection was carried out using a questionnaire sheet. The data that has been collected is then processed and analyzed using the SPSS Statistics Program version 25.0 and analyzed using the Chi-Square test. Results: there is an influence of 5S practice by midwives on the comfort of pregnant women when carrying out examinations with a value of ρ = 0.003. Conclusion:. There is an influence of 5S practices by midwives on the comfort of pregnant women during examinations